(3GdCdajI GdabgjI GdeSJWQaIs - (3GdCYQLj, GdMSjfj, GdcGXej, eMSf Hf MSf Hf GdeQJVi, J(B1227(3g`s ((3eTgO GdcGXes)
(3ChdgG (B:s
(3SHMGfg ef eMSf HGdfYe (B.... (3hHYO gPj OQQ HgjI CQLhRI CdajI abgjI (B*** (3fXeJ JSgjdG dVHW GdWGdH hGddg CLh ZGjI GdeWGdH (B...s
(3BNQgG (B:s
... .. (3ebJhd aMd GdEHd EPG GZJde aj GdGHJOGA UGMHg de jYde (B*** (3hgcPG eUQhY fbQ eQcHI ef RLQ ef jZTGg OaYG aGfJHg (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 286s
(3GdPQjYI (B16 \1300s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis